Geographical Atlases and activate their role in the Educational process: Between reality and expected - Fayez, Fatemah Mohmmed (Journal of Humanities & Social Sciences, 2020)
This cartographic study aimed to show the importance of geographic atlas as an educational tool that contributes to building spatial awareness and difficulties that prevented its use in teaching social education in general and geography in particular in general education schools as a supporting reference in general education and the most important technical elements of atlas maps to achieve effective cartographic communication for the user, Or the recipient according to the educational stage and age to which he belongs.The opinions of some teachers and students were also reviewed through the field، where an experimental approach was relied upon to experiment with some presentation tools and graphic symbols in a sample of atlases in order to find out the most suitable for student samples and the most suitable for their level of inclinations. the reasons that led to this kind of deficiency in understanding the purpose of the design of the atlas for the teacher and the studentThe views of some teachers and students were reviewed through the field and it was clear through the presentation and evaluation of users of some atlases and the level of acceptance towards the use of educational atlas in Saudi Arabia. It was found through the use of the critical curriculum and the presentation of the status quo of the Saudi educational atlas in the educational process the students are still experiencing some difficulties during their study of social education material these reasons have been identified and attempted to avoid them by raising awareness of the importance of the atlas and developing students' skills to understand its contents, It shows that atlases are not used in the educational process despite their cognitive importance, Most of the opinions tended to the need to activate the role of the Atlas as an educational means aimed at improving the delivery of geographic and historical information by the teacher and expand students' understanding of the understanding These opinions were also thoroughly analyzed statistically by relying on the descriptive and analytical method to know the deficiencies in the available atlases that prevented it from being used in teaching by teachers and students, This approach was also used to evaluate the results of the questionnaires conducted on the sample of the study from (students، teachers and owners of experience), Where the Sample was agreed on the possibility of benefiting from the atlas in the educational process more broadly، and the study was concluded with the presentation of results and recommendations.
Keywords: atlas; map; cartography; cartographic communication; presentation tools